Behavior Of The Store Head With Employee Behavior In Increasing Indomaret Customer Satisfaction - Nugraha, Teguh Arya; Ikbal, Muhammad; Hermawan, Abdul Jalil (ann4publisher@gmail.com, 2025)
Organizational communication is one of the vital elements in the management and operation of retail stores, including in the Indomaret rest area KM 229 B Kanci Pejagan Toll Road. One of the important parts of retail store management and operations, including Indomaret rest areas, is the organizational communication of a store head with employees and vice versa. Good service is the result of good communication between a coconut shop and employees, as well as efficient procedures. Indomaret faces problems such as consumers wanting to be served immediately, incomplete goods sold, unsatisfactory service, and price differences between shelves and cashier computers. This study aims to understand why organizational communication between store heads and employees in Indomaret rest areas is vital in improving service quality and good service results to consumers (consumer satisfaction); this research is expected to provide practical insights for Indomaret management in creating a communicative and collaborative work environment for superior customer service. This research method uses a qualitative approach to gain an in-depth understanding of the communication between store heads and employees in Indomaret rest areas which focuses on a thorough understanding of social issues based on realistic, detailed, and complex conditions. Based on the research results, it was found that the head of the Indomaret rest area store prioritizes the communication style in the organization by using—overarching Communication Patterns or Stars.